PENGARUH STRES KERJA TERHADAP TURNOVER INTENTION DENGAN DUKUNGAN SOSIAL SEBAGAI VARIABEL PEMODERASI - Putra, I Gede Aditya Pradana; Surya, Ida Bagus Ketut (E-Jurnal Manajemen, 2020)
The purpose of this study is to find empirical evidence of the effect of work stress on turnover intention with social support as a moderating variable on employees The object of this study is Turnover Intention on De vins sky Hotel Seminyak. Data collection method used was a questionnaire method. Data analysis technique used in this research is descriptive analysis technique. Hypothesis testing uses multiple linear regression analysis, Moderated Regression Analysis (MRA). Based on the results of the analysis shows that work stress has a positive and significant effect on turnover intention at De vins sky Hotel Seminyak Bali. Social Support has a negative and significant effect on turnover intention at De vins sky Hotel Seminyak Bali. Social support is able to moderate (weaken) the relationship between work stress and turnover intention at De vins sky Hotel Seminyak Bali. Keywords : work stress, social support, turnover intention